2019
DOI: 10.1111/eje.12436
|View full text |Cite
|
Sign up to set email alerts
|

Work, Stress and Play: Students’ perceptions of factors impacting on their studies and well‐being

Abstract: Introduction This study gathered information about life outside of the course for undergraduates studying at the School of Dentistry, Cardiff University. The aim was to explore how these external factors to the course may affect an individual’s academic performance and well‐being. Materials and Methods A cross‐sectional study design was used. An online questionnaire designed for the purpose of the study was used to capture (quantitative and qualitative) data. Questions with dichotomous options, a range of stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Potentially even worsening this situation, the updated curriculum coming into effect in fall 2020 may even increase the workload for students. With sports activities obviously not diminishing as a result of attending dental school, students try to maintain a healthy work‐life balance 11 and to counteract their risk for mental disorders 8,9 . Given that dental students seem to focus on natural science early on emphasising related school subjects where possible, it might be an option to reduce the workload in those areas during preclinical training and ensuring minimum requirements as part of an admissions test, instead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially even worsening this situation, the updated curriculum coming into effect in fall 2020 may even increase the workload for students. With sports activities obviously not diminishing as a result of attending dental school, students try to maintain a healthy work‐life balance 11 and to counteract their risk for mental disorders 8,9 . Given that dental students seem to focus on natural science early on emphasising related school subjects where possible, it might be an option to reduce the workload in those areas during preclinical training and ensuring minimum requirements as part of an admissions test, instead.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports can be found in the literature proving that dental students have higher levels of depression, anxiety or stress than the general population, 8,9 a problem for which integrated, active‐learning curricula 10 and concepts ensuring proper work‐life balance 11 may provide some relief. Due to the interdependent relationships between students, patients, instructors and administrators, 12 novel curricula should ensure the creation of an educational environment which is satisfying to future dentists 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study supported Hypothesis 3, proposing that positive expectations regarding future financial security were found to be positively associated with students' well-being. According to Jenkins, Johnson & Ginley (2019),…”
Section: Socioeconomic Characteristics Associated With University…4114mentioning
confidence: 99%
“…Elani et al conducted a systematic review which concluded that the pressure induced on dental students throughout undergraduate training was correlated with unfortunate effects on well‐being 4 . Students have varying personal lives and circumstances, hence must strive for a healthy balance of these influences with the nature of their degree 5 . A qualitative study based in Hong Kong suggested that the clinical transition in undergraduate training can pose stress, affecting clinical performance and confidence due to gaps in knowledge 6 .…”
Section: Introductionmentioning
confidence: 99%